2010 International Electron Devices Meeting 2010
DOI: 10.1109/iedm.2010.5703405
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low power TFTs with 10 nm stacked gate insulator fabricated by nitric acid oxidation of Si (NAOS) method

Abstract: We have succeeded in fabrication of ultra-low power poly-Si based thin film transistors (TFTs) with 10 nm gate insulators and 1 V driving voltage. An ultrathin interfacial SiO 2 layer formed in 68 wt% nitric acid (HNO 3 ) aqueous solutions at 120˚C decreases a gate leakage current by two orders of magnitude, resulting in a high on/off ratio of 10 9 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Simple immersion of Si in HNO 3 solutions with a concentration higher than 68 wt% can form a 1.1∼1.4 nm thick SiO 2 layer with a low leakage current density and a low interface state density. [11][12][13][14][15] Due to excellent interfacial characteristics of the NAOS SiO 2 layer, application to thin film transistors by the formation of ultrathin NAOS SiO 2 /plasma-enhanced chemical vapor deposition (PE-CVD) SiO 2 stacked gate dielectric structure leads to excellent device characteristics such as high on/off ratio of 10 9 , low sub-threshold swing value of 70∼80 mV/dec., and low driving voltage of 1∼3 V. [16][17][18] Mihailetchi et al applied the NAOS method to n-type single crystalline Si-based solar cells, and found that insertion of the NAOS SiO 2 layer between the Si substrate and the silicon nitride anti-reflection layer greatly increased the conversion efficiency, and improved the quantum efficiency of short-wavelength light due to the surface passivation z E-mail: h.kobayashi@sanken.osaka-u.ac.jp effect. 19 Grant and McIntosh reported that nitric acid oxidation considerably decreased a Si surface recombination velocity after annealing in nitrogen at 1100 • C. 20 In the present study, the NAOS method with nitric acid of high concentration, i.e., 68% and 98%, has been used to increase the minority carrier lifetime of Si and thus to improve the conversion efficiency of crystalline Si solar cells.…”
mentioning
confidence: 99%
“…Simple immersion of Si in HNO 3 solutions with a concentration higher than 68 wt% can form a 1.1∼1.4 nm thick SiO 2 layer with a low leakage current density and a low interface state density. [11][12][13][14][15] Due to excellent interfacial characteristics of the NAOS SiO 2 layer, application to thin film transistors by the formation of ultrathin NAOS SiO 2 /plasma-enhanced chemical vapor deposition (PE-CVD) SiO 2 stacked gate dielectric structure leads to excellent device characteristics such as high on/off ratio of 10 9 , low sub-threshold swing value of 70∼80 mV/dec., and low driving voltage of 1∼3 V. [16][17][18] Mihailetchi et al applied the NAOS method to n-type single crystalline Si-based solar cells, and found that insertion of the NAOS SiO 2 layer between the Si substrate and the silicon nitride anti-reflection layer greatly increased the conversion efficiency, and improved the quantum efficiency of short-wavelength light due to the surface passivation z E-mail: h.kobayashi@sanken.osaka-u.ac.jp effect. 19 Grant and McIntosh reported that nitric acid oxidation considerably decreased a Si surface recombination velocity after annealing in nitrogen at 1100 • C. 20 In the present study, the NAOS method with nitric acid of high concentration, i.e., 68% and 98%, has been used to increase the minority carrier lifetime of Si and thus to improve the conversion efficiency of crystalline Si solar cells.…”
mentioning
confidence: 99%